2012
DOI: 10.1016/j.visres.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Fixation light hue bias revisited: Implications for using adaptive optics to study color vision

Abstract: Current vision science adaptive optics systems use near infrared wavefront sensor ‘beacons’ that appear as red spots in the visual field. Colored fixation targets are known to influence the perceived color of macroscopic visual stimuli(Jameson, D. and Hurvich, L. M., 1967. Fixation-light bias: an unwanted by-product of fixation control. Vis. Res. 7, 805 – 809.), suggesting that the wavefront sensor beacon may also influence perceived color for stimuli displayed with adaptive optics. Despite its importance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
(53 reference statements)
5
10
0
Order By: Relevance
“…While this strategy allows excellent optical correction, so long as the distance between the beacon and stimulus is on the order of 1° or less (Bedggood, Daaboul, Ashman, Smith, & Metha, 2008), even a dim, displaced beacon can significantly impact perception. For example, Hofer et al (2012) found that a 1 μW, 840 nm beacon caused significant shifts in red-green appearance for small point stimuli, similar to those previously described for large stimuli when using colored fixation targets (Jameson and Hurvich, 1967). …”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…While this strategy allows excellent optical correction, so long as the distance between the beacon and stimulus is on the order of 1° or less (Bedggood, Daaboul, Ashman, Smith, & Metha, 2008), even a dim, displaced beacon can significantly impact perception. For example, Hofer et al (2012) found that a 1 μW, 840 nm beacon caused significant shifts in red-green appearance for small point stimuli, similar to those previously described for large stimuli when using colored fixation targets (Jameson and Hurvich, 1967). …”
Section: Introductionsupporting
confidence: 78%
“…We modified an existing adaptive optics system (Hofer, et al 2012) to accommodate a long wavelength 980 nm beacon (super luminescent diode, SLD, QPhotonics LLC) instead of the original, more typical, 840 nm beacon (SLD, Volga Technology Ltd.). Figure 1 describes the current system.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations